Knowledge, practices, and barriers of surgical items counting among perioperative team in public hospitals, Tshwane district Gauteng province - Rasweswe, Melitah M. (University of Pretoria, 2025)
Dissertation (MNur (Nursing Science))--University of Pretoria, 2024.